Mid-term outcome of children with latent rheumatic heart disease in eastern Nepal. Issue 1 (5th April 2021) - Shrestha, Nikesh Raj; Bruelisauer, Dorothea; Uranw, Surendra; Mahato, Rajan; Sherpa, Kunjang; Agrawal, Krishna; Rothenbühler, Martina; Karki, Prahlad; Pilgrim, Thomas
Abstract : Introduction: Systematic echocardiographic screening of children in regions with an endemic pattern of rheumatic heart disease allows for the early detection of valvular lesions suggestive of subclinical rheumatic heart disease. The natural course of latent rheumatic heart disease is, however, incompletely understood at this time. Methods: We performed a prospective cohort study of children detected to have echocardiographic evidence of definite or borderline rheumatic heart disease according to the World Heart Federation Criteria. Results: Among 53 children found to have definite (36) or borderline (17) rheumatic heart disease, 44 (83%) children underwent follow-up at a median of 1.9 years (IQR 1.1–4.5). The median age of the children was 11 years (IQR 9–14) and 34 (64.2%) were girls. Among children with definite rheumatic heart disease, 21 (58.3%) were adherent to secondary antibiotic prophylaxis, 7 (19.4%) were not, information on adherence was missing in 2 (5.6%) children and 6 (16.7%) were lost to follow-up. Regression of disease was observed in 10 children (27.8%), whereas 20 children (55.6%) had stable disease. Among children adherent to secondary prophylaxis, seven (33.3%) showed regression of disease. Among children with borderline disease, seven (41.2%) showed regression of disease, three (17.6%) progression of disease, four (23.5%) remained stable and three (17.6%) were lost to follow-up. On univariate analysis, we identified no predictors of disease regression, and no predictors for lost to follow-up or non-adherence with secondary antibiotic prophylaxis. Conclusion: Definite rheumatic heart disease showed regression in one in four children. Borderline disease was spontaneously reversible in less than half of the children and progressed to definite rheumatic heart disease in one in five children. Trial registration number: NCT01550068 .